Neutrinoless Double Beta Decay: 2015 Review - Stefano Dell’Oro; Simone Marcocci; Matteo Viel; Francesco Vissani (Advances in High Energy Physics)
The discovery of neutrino masses through the observation of oscillations boosted the importance of neutrinoless double beta decay (0νββ). In this paper, we review the main features of this process, underlining its key role from both the experimental and theoretical point of view. In particular, we contextualize the 0νββ in the panorama of lepton number violating processes, also assessing some possible particle physics mechanisms mediating the process. Since the 0νββ existence is correlated with neutrino masses, we also review the state of the art of the theoretical understanding of neutrino masses. In the final part, the status of current 0νββ experiments is presented and the prospects for the future hunt for 0νββ are discussed. Also, experimental data coming from cosmological surveys are considered and their impact on 0νββ expectations is examined.